2022
DOI: 10.3904/kjim.2022.015
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of lumican on human bone health: clinical evidence using bone marrow aspirates

Abstract: Background/Aims: Lumican, a small leucine-rich proteoglycan, has shown osteoprotective effects by synchronously stimulating bone formation and suppressing bone resorption. To clarify the role of lumican in human bone metabolism, the association between lumican concentrations and osteoporosis-related phenotypes was evaluated using bone marrow (BM) samples directly reflecting local microenvironments.Methods: BM aspirates were obtained from 77 patients during hip surgery for either fragility hip fractures (HF) (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…LUM (Lumican) is a member of the small leucine-rich proteoglycans family, located on chromosome 12q21.3-q22 [ 15 , 16 ]. LUM is predominantly expressed in connective tissues and participates in tissue reconstruction [ [16] , [17] , [18] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LUM (Lumican) is a member of the small leucine-rich proteoglycans family, located on chromosome 12q21.3-q22 [ 15 , 16 ]. LUM is predominantly expressed in connective tissues and participates in tissue reconstruction [ [16] , [17] , [18] ].…”
Section: Introductionmentioning
confidence: 99%
“…LUM (Lumican) is a member of the small leucine-rich proteoglycans family, located on chromosome 12q21.3-q22 [ 15 , 16 ]. LUM is predominantly expressed in connective tissues and participates in tissue reconstruction [ [16] , [17] , [18] ]. Recent studies have demonstrated that LUM is involved in various tumor-related cellular processes such as epithelial-mesenchymal transformation, cell proliferation, migration, invasion, and adhesion [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%